FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KAPASITAS FUNGSI PARU PADA PEKERJA PENGELASAN DI PT. X KOTA SEMARANG TAHUN 2016 - Bintang Nurkhaleda; Siswi Jayanti; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Lung capacity is a combination of several lung volumes, namely inspiration capacity, functional residue capacity, vital capacity, and total lung capacity. The result of welding activity is in form of various metal combinations; they can be gas and fume particle. If the smoke welding particle inhales, it will be restrained by the nose hair and hair tube inhalation. While the smooth particle enter and adhere to the lung; it will cause disorders of lung function. The purpose of this research was to know several factors which are related to the functions of lung capacity of the welders in PT. X Semarang. The method of this research was Explanatory Research by cross sectional approach. The object of this research was 37 respondents of the welder in production unit. The source of the primer data was conducted by the result of interview, several questioners and the measuring of lung capacity by using Spiro meter. The data analysis used chi square test. The research result showed respondents with abnormal lung capacity by 37,8%. The bivariat analisis result showed there was no relationship between work period (p-value 1,001) by the lung function. There was a relationship between smoking habit (p-value 0,001), using mask (p-value 0,001) and the work area (p-value 0,001) by the lung function capacity. The company should apply smoking ban when the welder are working in the work environment, provide the use of mask and catridge filter and make a work shift for the welder in the indoor area in order to be spared from the dangerous of exposure.